Geological study of the Signal Hill Au-As-Sb deposits, Archaean Tati schist belt, Northeast Botswana. - Audet, Marc-Antoine (My University, 2016)
The Signal Hill Au-As-Sb deposits lie in the uppermost formations of the Archaean Tati Schist belt, located in northwest Botswana. The surface exposures of the potentially economic deposits are confined to three main zones: “A” Zone, “B” Zone and the “F” Zone. The “A” Zone and the “B” Zone are found with the sedimentary assemblage of the Last Hope Formation, while the “F” Zone lies within the underlying volcanic Penhalonga Formation. : [Abbreviated Abstract. Open document to view full version]
This thesis is submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, for the Degree of Master of Science. January 1995.
Keywords: Geology--Botswana; Geology, Structural--Botswana